(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Today, in the world, a system of qualitative provision of public order and security has been created only in economically powerful countries. This is because effective work is being carried out to qualitatively ensure public order and security. In this regard, the main force that destroys the future of young people who are the driving force behind the development of each state is narcotic drugs, their analogues or psychotropic substances.